Housing rural-urban migrants in Katutura: A transition towards a place in which "we want to stay" - Valombweleni, Isai Ndakalako (School of Architecture, Planning and Geomatics, 2023)
The focus of this dissertation is on housing for rural-urban migrants in Katutura translated in the Otjiherero language as “a place where we do not stay”, is a former Black African township in Windhoek Namibia. Katutura is characterised by the NE51/9 house type (NE stands for Non-European, 51 stands for the year of design, and 9 for the specific type), and by the lack of social space and community cohesion that typically accompanies this type of urban settlement across Southern Africa. This urban condition contributes to a loss of identity for these new city dwellers and difficulties in integrating into their new living conditions. The purpose of the dissertation is to offer an alternative housing model that aims to facilitate a transition from rural to urban conditions. The model acknowledges the significant aspects of both rural and urban realities in a sustainable way addressing issues of identity, integration and food security. The research proposes to change the name of the suburb to Tukara (a place we want to stay) as a counter strategy towards the Apartheid government's spatial planning strategies in Katutura, which made it “a place where we do not stay”. The studies will be looking at the spatial justice theory to address the spatial inefficiency of the NE51/9 house type, as a framework for developing counter strategies for spatial justice. Flexible housing and Spatial agency principles are strategies for providing quality, and affordable housing for people of rural origins. This integration is activated through the hybridization of ways in which ruralurban migrants have adapted their NE51/9 houses to accommodate their needs with vernacular traditional practices, and ways of making from rural life. The hybridization of aspects from the rural and urban helps create a sense of identity, and belonging for rural-urban migrants in a contemporary urban environment with rapid new technological developments and globalization in the construction industry.